Difusão e acesso em locais de memória da cidade de Belém: um estudo sobre os registros documentais da Cabanagem - ARAUJO, Rodrigo Lopes de (2021)
Considering the social role of archives in information and knowledge production, this paper is directed towards the understanding of the formation of the Cabanagem archive, popular movement in Pará in the first half of the 19th century, with political, economic and social meanings. It was sought, identify the practices used by archival institutions custodians of such records in the processes of such collections. The motivation to study the theme is due to the perception of a relative lack of knowledge of the society regarding Cabanagem. The analysis was based on the bibliographical production related to the diffusion collection, in addition to documentary research to be carried out in previously selected. The results were quite satisfactory in that Most of the institutions surveyed which understand the importance of promoting access to the information they have custody, and verify that the Cabanagem is still very much present in the research lines of these institutions, where they frequently promote actions aimed at disseminating this theme. It is hoped to contribute to the visibility of memory of our region, especially those that maintain and preserve the Cabanagem and, at the same time, assist search for primary sources about this movement.